THE ROLE OF THE SECURITY SERVICES IN PREVENTING POLITICAL COUPS - Trbojević, Milovan; Svirčević, Branislav (The Policy of National Security, 2025)
States achieve their foreign policy goals and intentions in different ways, including methods contrary to the norms of international law. Namely, suppose one wants to destabilize a country's economic, political, security and social-social system to implement one's own will, intentions, and interests. In that case, subversive activity is one of the most effective mechanisms. Such activities often cause and maintain various crises, including coups, which aim to impose one's own will on other countries and direct their socio-political flows according to national interests. Countries that carry out coups and other secret actions implement them through their intelligence institutions, which is why the target countries must have strong security and counterintelligence organizations which will prevent such activities. States that seek to maintain their sovereign domestic and foreign policies often become the target of coups and other subversive activities. Therefore, their security apparatus must continuously detect and stop such activities with preventive and repressive methods. Accordingly, the security services have always been a decisive support factor in realising internal political goals and protecting the holders and institutions of state power. Bearing that in mind, the subject of this paper is the research and analysis of the role of the security service as an important segment of the state's security-intelligence system in opposing subversive activity towards the home state with an emphasis on preventing a political coup. The paper examines the ways and means of the security services that oppose political coups.
Keywords: security services; counterintelligence services; political coups; national values and interests